1990
DOI: 10.1097/00000658-199009000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of APACHE II for Cost Containment and Quality Assurance

Abstract: APACHE II (an acronym formed from acute physiology score and chronic health evaluation) has been proposed to limit intensive care unit (ICU) admissions ('cost containment') and to judge outcome ('quality assurance') of surgical patients. To judge its performance, a 6-month study of 372 surgical ICU patients was performed. When patients were divided by mean duration of stay, mortality rates rose from 1% (short stay) to 19% (long stay) (p less than 0.001) for patients with APACHE II scores less than 10, but decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
37
0
2

Year Published

1994
1994
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(39 citation statements)
references
References 11 publications
0
37
0
2
Order By: Relevance
“…Furthermore, they are difficult to use on a daily basis. In addition, it has been reported that APACHE II does not always reflect the severity of MODS in patients belonging to certain groups [21,22,23]. In fact, Civetta et al [21] found that neither the length of stay in the ICU nor mortality correlated with APACHE II for surgical ICU patients.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Furthermore, they are difficult to use on a daily basis. In addition, it has been reported that APACHE II does not always reflect the severity of MODS in patients belonging to certain groups [21,22,23]. In fact, Civetta et al [21] found that neither the length of stay in the ICU nor mortality correlated with APACHE II for surgical ICU patients.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, it has been reported that APACHE II does not always reflect the severity of MODS in patients belonging to certain groups [21,22,23]. In fact, Civetta et al [21] found that neither the length of stay in the ICU nor mortality correlated with APACHE II for surgical ICU patients. Similarly, Cerra et al [23] reported that APACHE II did not always predict manifestations of MOF and mortality; they noted, instead, that changes over time in four parameters, PaO 2 /FIO 2 ratio, creatinine, bilirubin and lactate (the latter two not included in APACHE II) were more useful in predicting death.…”
Section: Discussionmentioning
confidence: 98%
“…Grading the severity of acute peritonitis has assisted in decision making and has made therapy ameliorated for the management of severely ill patients [4]. The assessment of risk considering various clinical parameters to evaluate new therapies, monitor resource utilization, quality of care improvement is of immense value at present [5,6]. It is very difficult to evaluate severity, decide treatment options, therapeutic approach for the acute generalized peritonitis caused due to perforation due to its broad overlapping classification.…”
Section: Discussionmentioning
confidence: 99%
“…[4] The assessment of risk considering various clinical parameters to evaluate new therapies, monitor resource utilization, quality of care improvement is of immense value at present. [5,6] Many scoring systems are available that helps to measure & stratify the condition of critically ill patients and thus helps the clinicians in better resource allocation as per the needs of the patient and feasibility of outcome expected. [7] Amongst them APACHE II (Acute Physiological and Chronic ill Health Evaluation), is widely used.…”
mentioning
confidence: 99%